Dealing with racism - Lacey, Jane (London : Franklin Watts, 2017)
Sometimes you can sort out a problem on your own. But sometimes you need to ask for help. This book helps young children to make this decision and find out about and understand racism. It features seven case studies from children who have a range of racism problems from a girl who is being left out because she is Muslim to the new boy in school from another country who is struggling to fit in. The end of the book features a short playscript to act out and discuss. The book has engaging illustrations throughout. In this series case studies combine with sensible, practical advice to help children find out what to do in difficult situations.
Keywords: Children literature - Non-Fiction